Learning C# by developing games with Unity 2020 an enjoyable and intuitive approach to getting started with C# programming and Unity - Ferrone, Harrison (Packt Publishing, 2020)
This fifth edition of the popular C# guide helps you learn the building blocks of C# language, right from variables to classes and exception handling. After getting to grips with the basics of C# programming, it takes you through the world of Unity game development and how you can apply C# knowledge using game development examples.